Disturbed nights and 3-4 month old infants: the effects of feeding and thermal environment. Issue 5 (May 1990) - Wailoo, M P; Petersen, S A; Whitaker, H
Abstract : Parents completed a prospective diary of a night's sleep for 87, 3-4 month old infants at home whose body temperatures were continuously recorded. We found that about half of the babies disturbed their parents in the night. Breast fed babies were more likely to wake parents in the middle of the night. The babies who disturbed their parents in the middle of the night were significantly more heavily wrapped in significantly warmer rooms. We suggest that discomfort from efforts at active thermoregulation in warm environments may lead some babies to disturb their parents at 'unsocial hours'.